2014
DOI: 10.1080/00028487.2014.892534
|View full text |Cite
|
Sign up to set email alerts
|

Is Mobility a Fixed Trait? Summer Movement Patterns of Catostomids using PIT Telemetry

Abstract: Fish populations are composed of a mixture of sedentary and mobile individuals, but it is not clear whether movement behavior is plastic or fixed for individuals and what proportion of the population exhibits mobile behavior. To investigate the mobility and movement patterns of two common species of suckers, the Sonora Sucker Catostomus insignis and the Desert Sucker Catostomus clarkii, in the Gila River of western New Mexico, we tracked 449 individuals over three summers using passive integrated transponder (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Rapid recolonization of formerly dry habitat is likely to occur after the cessation of drought (Lennox, Crook, Moyle, Struthers, & Cooke, ). High flow events are known to induce dispersal of native fishes elsewhere in the Colorado River Basin for increased foraging, spawning, or exploring activities (Booth, Flecker, & Hairston, ; Cathcart, Gido, & McKinstry, ; Cross et al, ), leading to decreased probability of local extinction (Budy, Conner, Salant, & Macfarlane, ). Years with the highest flow anomalies are also times when extreme spring floods or summer monsoons have occurred, and may have been detrimental to non‐native species populations (Bestgen, Wilcox, Hill, & Fausch, ; Gido, Propst, Olden, & Bestgen, ; Rogosch et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Rapid recolonization of formerly dry habitat is likely to occur after the cessation of drought (Lennox, Crook, Moyle, Struthers, & Cooke, ). High flow events are known to induce dispersal of native fishes elsewhere in the Colorado River Basin for increased foraging, spawning, or exploring activities (Booth, Flecker, & Hairston, ; Cathcart, Gido, & McKinstry, ; Cross et al, ), leading to decreased probability of local extinction (Budy, Conner, Salant, & Macfarlane, ). Years with the highest flow anomalies are also times when extreme spring floods or summer monsoons have occurred, and may have been detrimental to non‐native species populations (Bestgen, Wilcox, Hill, & Fausch, ; Gido, Propst, Olden, & Bestgen, ; Rogosch et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Increased and continuous use of remote monitoring via PIT antennas in large river networks spanning multiple jurisdictions (i.e. Columbia and Colorado river basins) provides unique opportunities for exploring dynamic long-term network-wide movement patterns of imperiled fishes with special consideration to the interfaces among mainstem, floodplain and tributary habitats (Booth, Flecker, & Jr, 2014;Galat & Zweimüller, 2001;PTAGIS, 2011). Diverse movement patterns within fish communities at mainstem-tributary confluences can continuously link different streams via life histories that divide a shared space across time (Benda et al, 2004;Braaten & Guy, 1999;Kiffney et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Though we were unable to evaluate survival of tagged fish, we found only eight PIT-tagged fish (0.30% of all tags implanted) and no known caudal-punched fish that were incapable of continuing upstream immediately after initial handling. Some studies have looked directly at survival of captive PIT-tagged adult catostomids and have found uniformly high survival rates (Burdick and Hamman 1993;Ward and David 2006;Hewitt et al 2010;Booth et al 2014), except for Ficke et al (2012), who found that survival was less than 44% for juvenile White Suckers under 172 mm TL . At least a portion of the fish in all those studies were tagged in a similar body location to ours, but some were tagged with PIT tags twice the size (23.1 × 3.9 mm) of the ones we used.…”
Section: Discussionmentioning
confidence: 99%